KONSTESTASI PENDIDIKAN ISLAM DI LOMBOK: NAHDLATUL WATHAN VIS A VIS SALAFI-WAHHABI - Muharir, Muharir (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract This article will discuss the contestation of Islamic Education in Lombok in post reformation 1998. Namely the contestation of madrasas and schools managed by the Islamic organization Nahdlatul Wathan (NW) and the Salafi-Wahhabi community in East Lombok. By using  qualitative approach in the form of library research, this article focuses on discussing some issues: first, the genealogy of the Nahdlatul Wathan and Salafi Madrasas. Second, Madrasas as the basis for the construction of  aswaja and Salafi-Wahhabi ideologies. Third, the pattern of contestation between Nahdlatul Wathan (NW) and Salafi-Wahhabi. This research  shows: First, the Nahdalul Wathan and Salafi madrasas in Lombok were genealogically founded by Middle Eastern Alumni (haramain). Second, curriculum design both in NW and Salafi madrasas uses for strengthening the ideology, identity and militancy of their own group. Third, the pattern contestation of Nahdlatul Wathan Islamic education vis a vis Salafi-wahhabi does not take place formally in madrasas, but uses the medium of mosques and virtual da'wah as well.